The Development of Digital Book Media Materials for Asean Countries Learning in Elementary School - Agita Ayu Diah Pitaloka; Rd. Deti Rostika; Yona Wahyuningsih (International Journal of Learning and Instruction (IJLI), 2022)
This research is motivated by optimizing ASEAN material in sixth grade Elementary School in social studies learning through digital book media, the use of digital book media is used because of the lack of use of learning media during teaching and learning activities, then the use of media can provide interest and motivation to learn in students with a good display. interesting. The purpose of this study is to develop digital book media for ASEAN countries, and to find out the results of the feasibility of the media through experts, teacher users and sixth grade elementary school students. The method used in this research is the D&D method with the ADDIE research procedure. Based on the research results, there are validation assessments from various experts, including social studies material experts, media experts, and linguists. Based on the results of the assessment of material experts, media experts, and linguists, it can be concluded that the Digital Book Media of ASEAN Countries is in the "Very Feasible" interpretation based on the indicators contained in the validation of material experts, media experts, and linguists, namely the suitability of the material, accuracy material, material clarity, presentation support, learning presentation, digital book size, cover design, content design, readability, usability, straightforwardness, communicativeness, language suitability, and the use of terms to be used as media in social studies learning for sixth grade. Meanwhile, the results of the research on teacher and student users received a "Very Feasible" interpretation based on indicators for users including material suitability, material clarity, material usability, design, readability, language suitability, usability, ease of use, materials, media, and language. It can be concluded that this digital book media is very suitable to be used in social studies learning, especially on the material of ASEAN countries in sixth grade elementary school.               Keywords: D&D Research, ADDIE Procedure, Digital Book Media, ASEAN Countries